Analysis mixed-mode fracture toughness (mode I/II) of a single layer graphene sheet by finite element methods simulation - Nguyen, Duc Tai; Nguyen, Minh Ky (Journal of Technical Education Science, 2018)
The mode I and mode II fracture behavior of a single-layer graphene sheet (SLGS) containing a center crack was characterized with the results of an finite element method (FEM) and an analytical model. Finite element method based micromechanical analysis is used to understand the fracture behavior of functionally SLGS. The in-plane shear fracture of a cellular material was analyzed theoretically for deriving the KIC, KIIC of SLGS, and FEM results were obtained. Mixed-mode fracture of armchair direction graphene sheet was studied for various angle mode I/II ratios. The effect of mixed-mode loading on the Arcan specimen was investigated, all the systems considered in this study mimic real service conditions. The mixed-mode fracture criterion was determined, and the obtained fracture envelope was in good agreement with that of another study.